Effects of silver nanoparticles on germination and seedling characteristics of Oriental beech (Fagus orientalis) seeds - Özel, Halil Barış; Sevik, Hakan; Yıldız, Yafes; Cobanoglu, Hatice (BioResources, 2024)
Nowadays, the applications of nanotechnology are increasing in various fields such as information technology, energy, the medical sector, and agriculture. Nanotechnology has proved its ability to solve problems in agriculture and related industries. Establishing the impact of nanoparticles on various ecosystems has become a primary research topic, but studies on forest ecosystems and trees are quite limited. This study examined the effects of silver nanoparticles on the germination parameters of oriental beech seeds and established their toxic threshold values. Silver nanoparticles were applied at concentrations of 200, 400, 600, 800, and 1000 mg/L to oriental beech (Fagus orientalis) seeds collected from 10 different populations in order to identify the germination rate, germination percentage, seedling height, root collar diameter, plumula length, radicle thickness, and radicle length parameters. The results revealed that silver nanoparticles have a negative effect on germination and seedling parameters of oriental beech seeds, and that this effect is clearly seen in the germination rate at 20 mg/L levels and in seedling characters starting from 60 mg/L dose, causing a decrease of 13% in germination rate, 24% in germination percentage, 40% in plumula length, and 30% in radicle length. The Kahramanmaras-Andirin population was found to be the most affected by nanoparticles, while the Bursa-Inegol and Ordu-Akkus populations were the least affected.
Keywords: nanoparticle; Germination; Ag; ag; Fagus Orientalis; Nanoparticle; Heavy-Metal Concentrations; germination; Organ; fagus orientalis; Fagus orientalis; TP248.13-248.65; Biotechnology; 2. Zero hunger; 15. Life on land; 13. Climate action